Reproductive Rights: A Comparative Analysis of Abortion Regulations and the Case of Reform in the Republic of Benin - Konnon, Romeo (Medicine, Law & Society, 2024)
Induced abortion remains controversial due to traditional, moral, political, and religious reasons. Although the common opinion about the illegality of abortion is indicated in medical conditions, its regulation varies widely according to the country. Abortion is available to women on request in many countries, while in others, there is restriction or prohibition altogether. In the contest when some countries end the nationwide right to abortion, the Republic of Benin in 2020 broadened the social grounds, allowing abortion up to 12 weeks of gestational age. This paper aims to overview abortion legislation in selected countries and to compare them to the reform in the Republic of Benin, which became one of the several African countries broadly permitting abortion within 12 weeks of amenorrhea.